Perkembangan Surabaya Sightseeing and City Tour Bus Sebagai Promosi Wisata di Kota Surabaya - Indriana, Desvidyauralia Kartika; Rahmatin, Leily Suci (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
The city of Surabaya is a tourist destination that has tourism potential in history, beaches, culinary tourism, cultural performances and others. The variety of tourism potential that the city of Surabaya has, encourages the city to continue to innovate in its tourism development so that it can be known by the wider community. The existence of the SSCT Bus is a manifestation of the innovation of the City of Surabaya to be able to introduce tourism through a different experience by riding a bus. This research aims to determine the development of SSCT Bus in promoting tourism in Surabaya. The methods used in this research are field observation, interviews and literature study. The results of the analysis show that SSCT Bus operations are still hampered by ticket reservations and limited quotas on SSCT Buses. Apart from that, SSCT Bus needs to pay attention to promotion through social media, namely creating a special Instagram account, which can focus more on the identity of SSCT Bus itself.